Application Of Public-Private Partnership Concept In A Tourism Destination: A Case Study Of Penang Hill - Mohd, Mohd Firdaus Habib (2018)
Sustainable management aspects of a hill station are directly related to the environment and the community. There are currently numerous management practices for hill station management. However, scant attention has been paid to the approach of partnership in the management of a tourism destination. Current PPP approach on Penang Hill were analyzed and comparison with The Habitat’s approach was done. The existing PPP concept has very limited association with the management of a corporation and its link to environmental protection. In order to explore this management approach, Penang Hill and Penang Hill Corporation (PHC) are chosen. Qualitative case study is used with in-depth interviews conducted with ten primary stakeholders of Penang Hill. The data collected was analyzed thematically. The study finds that The Habitat model of PPP on Penang Hill is more inclusive compared to the previous approach. The study also finds that the partnership should be extended to Non-governmental organizations (NGOs) and professional bodies and the concept of PPP should be Public, Private, NGO and Professional Bodies Partnership (PPNPP). With regards to environmental protection, the PPNPP concept is found to overcome the environmental threats and to guide PHC towards better management. The PPNPP concept is proposed as a management framework to guide the partnership between public, private, NGOs and professional bodies towards a sustainable management of Penang Hill.